A comparison of long-term fouling performance by zirconia ceramic filter and cation exchange in microbial fuel cells - Daud, S.M. (2019)
The long-term performance of non-ion selective separators, zirconia ceramic filter (ZCF) with a various pore size such as 0.14 Î¼m ZCF1, 150 kDa ZCF2 and 5 kDa ZCF3 were compared to commercial cation exchange membrane (CEM), Nafion 117 in microbial fuel cells. The ZCF3 generated the highest performance of 2800 Â± 14.5 mWmâ2 (5.9 Amâ2) compared to CEM: 1800 Â± 17.8 mWmâ2, 4.0 Amâ2. Meanwhile, the CEM exhibited maximum power decline during the reverse sweep (61.7) when analyzed using the bi-directional polarization method. The non-ion selective membranes displayed reduced in maximum power decline during the reverse sweep (ZCF1 50, ZCF2 40 and ZCF3 42.8). In addition, the ZCF3 showed the highest proton conductivity and water uptake, 0.863 Ã 10â1 Scmâ1 and 93.7 respectively, followed by ZCF2 (0.729 Ã 10â1 Scmâ1, 80.98), ZCF1 (0.624 Ã 10â1 Scmâ1, 73.99) and Nafion 117 (0.367 Ã 10â2 Scmâ1, 57.07). The ZCF3 appeared as an efficient material for electrochemical active bacteria, maintaining the high power of 1600 mWmâ2, compared to CEM: 600 mWmâ2 after eight monthsâ operation under batch mode. The long-term operation of MFCs was affected by the reduction of power output, caused by the increase in the thickness of the biofilm. Â© 2018 Elsevier Ltd